Employees retention among the workers in Kuala Lumpur and Selangor / Nik Sarah Hajar Mahmod - Mahmod, Nik Sarah Hajar (Faculty of Business and Management, 2020)
Employees will increase their loyalty to the company and become more productive when they feel highly motivated and committed to the organization. It allows them to gain competitive advantage, thus the organization tends to retain these employees for longer time of period. Issues such as high turnover could have an impact on organization’s performance and decreased the employee retention rate when employee have left the organization. This research is to determine the significant relationship between independent variables (compensation, working environment, career development, and employer branding) with dependent variable (employee retention). A self-administered questionnaire was distributed via Internet to the respondents which is the workers in Kuala Lumpur and Selangor by using convenience sampling techniques with the response rate of 384. This study used a Statistical Package for Social Sciences Version 22 (SPSS V22) in analyzing the data that been collected. This study using a Multiple Regression Analysis to answer the research objective where in this study found that compensation and career development shows significant relationship with employee retention, whereas working environment and employer branding are not significant. In future, the organization should improve the compensation package where it will attract and retain the best employee and implement the career development plan for employee to improve their skills to add more value growth in the organization.